EQ-5D: a plea for accurate nomenclature - Richard Brooks; Kristina S. Boye; Bernhard Slaap (SpringerOpen, 2020)
Abstract Between 1987 and 1990, the EuroQol Group developed a 5-dimension health-related quality of life instrument, originally known as 'the EuroQol instrument', which since 1995 has been called the 'EQ-5D'. For several years, 'the EuroQol instrument' and 'EQ-5D' were both deployed in published materials. In order to standardise nomenclature, the EuroQol Group agreed in 2001 on a terminology glossary containing 12 items; this was recently revised and augmented to include 22 items and can be found on the Group's website ( www.euroqol.org ). Since 2009, EQ-5D has been available in three versions: EQ-5D-3L, EQ-5D-5L, and EQ-5D-Y, where 3L stands for three levels, 5L for five levels, and Y for youth. Yet, almost 20 years after the original glossary was published, the instrument and its components continue to be inaccurately named in published materials. Two surveys - of arthritis applications, and 82 recent publications - found a variety of terms used to describe the instrument. Despite the instrument being named 'EQ-5D' for 25 years, and the terms 'EQ-5D-3L' and 'EQ-5D-5L' being established for a decade, variations of 'the EuroQol instrument' continue to be used as descriptors. The EuroQol Group's website contains advice on how to use EQ-5D, including nomenclature, and potential users are urged to consult the site. Since standardising nomenclature is crucial in the compilation of systematic reviews, the EuroQol Group would like to emphasise that 'EQ-5D' is not an abbreviation and is the correct term to use when referring to the instrument in general. In the interests of accuracy and good practice, users of the EuroQol family of instruments should employ the standard EQ-5D nomenclature when reporting and discussing their findings.